2022
DOI: 10.3389/fcell.2022.1011974
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific changes in Wnt signaling and neuronal differentiation in the developing mouse cortex after prenatal alcohol exposure during neurogenesis

Abstract: Fetal Alcohol Spectrum Disorder (FASD) encompasses an array of effects of prenatal alcohol exposure (PAE), including physical abnormalities and cognitive and behavioral deficits. Disruptions of cortical development have been implicated in multiple PAE studies, with deficits including decreased progenitor proliferation, disrupted neuronal differentiation, aberrant radial migration of pyramidal neurons, and decreased cortical thickness. While several mechanisms of alcohol teratogenicity have been explored, how s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Interestingly, a greater number of resilience than risk alleles, 16 vs 11, were found in these pathways, compared to those found in the RA metabolism pathway. This was a surprising result given that animal models have shown these pathways are directly impacted by PAE, and when perturbed can exacerbate PAE teratogenesis [80,81]. Although these PAEimpacted pathways can be viewed as independent of each other, they are co-dependent and function through defined signaling gradients [82].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a greater number of resilience than risk alleles, 16 vs 11, were found in these pathways, compared to those found in the RA metabolism pathway. This was a surprising result given that animal models have shown these pathways are directly impacted by PAE, and when perturbed can exacerbate PAE teratogenesis [80,81]. Although these PAEimpacted pathways can be viewed as independent of each other, they are co-dependent and function through defined signaling gradients [82].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is necessary to study in more detail the effects of PAE on the structure and function of regions involved in olfactory processing other than the OB, such as olfactory epithelium and olfactory cortex. Furthermore, while diverse in vivo and in vitro studies have elucidated various signaling pathways affected by PAE during brain development (Hashimoto-Torii et al, 2011;Mohammad et al, 2020;Fischer et al, 2021;Salem et al, 2021;Sambo et al, 2022), this type of research has so far been insufficient for the olfactory system. Understanding the molecules and pathways affected by PAE in the developing olfactory system could shed light on potential mechanisms underlying the etiology of abnormal sense of smell.…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence that excessive alcohol consumption extensively damages multiple organ systems, especially the CNS, as chronic alcohol use leads to permanent cognitive decline and motor deficits [109]. In vitro and in vivo studies have shown that prenatal alcohol exposure impairs the development of the newly formed cortex in the developing fetus [110,111], and chronic alcohol exposure reduces neurogenesis and enhances cell death in adolescents; these changes may not be alleviated until a substantial period of time after alcohol cessation [112,113]. High-dose alcohol exposure in young adult rats suppresses hippocampal neurogenesis, including by decreasing the number of type-1 NSCs and type-2a NPCs in the DG subgranular zone and FOS+ granule cells, and reduces synaptic plasticity [114].…”
Section: Alcohol and Stressmentioning
confidence: 99%